Combination HIV Prevention Strategy Implementation in El Salvador: Perceived Barriers and Adaptations Reported by Outreach Peer Educators and Supervisors - Meredith Buck; Julia Dickson-Gomez; Gloria Bodnar (SAGE Publishing, 2017)
El Salvador was one of three countries to receive funding from the Global Fund to Fight AIDS, Tuberculosis and Malaria to conduct a combination HIV prevention intervention among transwomen (TW), men who have sex with men (MSM), and commercial sex workers (CSW). Program evaluation revealed that prevention activities reached only 50% of the target population. The purpose of this study is to examine the barriers that Salvadoran educators faced in implementing the peer education as designed and adaptations made as a result. Between March and June 2015, 18 in-depth interviews with educators were conducted. Violence was reported as the biggest barrier to intervention implementation. Other barriers differed by subpopulation. The level of violence and discrimination calls into question the feasibility and appropriateness of peer-led interventions in the Salvadoran context and demonstrates the importance of implementation research when translating HIV prevention interventions developed in high-income countries to low- and middle-income countries.